Respuesta :

Answer:

a+b

Step-by-step explanation:

1/2(4a+6b) - 1/4(4a+8b)

= 4a/2 + 6a/2 - 4a/4 - 8a/4

=2a+3b-a-2b

=(2a-a)+(3b-2b)

=a+b

Answer:

a + b

Step-by-step explanation:

1/2 (4a+6b) - 1/4 (4a+8b)

Because 1/2 * (4a+6) / 1 = 4a+6 / 2 So we can write it as:

= (4a+6b) / 2 - 1/4 (4a+8b)

Factor our common term 2:

= 2*(2a+3b) / 2 - 1/4*(4a+8b)

Cancel 2:

= (2a+3b) - 1/4*(4a+8b)

1/4*(4a+8b) can be write as: 1/4 * (4a+8b) / 1

= (2a+3b) - (4a+8b) / 4

Factor out common term 4, we got:

= (2a+3b) - 4(a+2b) / 4

Cancel 4:

= (2a+3b) - (a+2b)

Break the bracket:

= 2a+3b-a-2b

= 2a - a + 3b - 2b

= a + b

Simplified

Hope this help you :3